(untitled) (Revista Educação, Artes e Inclusão, 2021)
This article is a case study of na experience inspired by the Triangular Approach in which 3rd year high school students at Mariano Martins State Public School (Fortaleza, CE) intervened artistically on the school walls. To discuss contemporary art teaching, the Triangular Approach and the school as a space for artistic production, we bring in thes study the contributions of Biasoli (1999), Ana Mae Barbosa (2014), Carvalho, Carolino (2010), Guimarães (2010), Pimentel (2006, 2010), Brissac (1998), Ostrower (1984) and Salles (2011). We aim to presente reflections on the teaching process and learning in Visual Arts from the experience in artistic intervention. Data were collected from the teacher’s field diaries, student portfolios, class footage, interviews and photographs, and interpreted from the perspective of thematic analysis. We realize that the Triangular Approach is a theoretical and methodological proposal for Art teaching that generates possibilities for the realization of artistic knowledge and that activities of school appropriation as a space for artistic production outline paths that are configured as potentialities for the realization of critical and reflective thinking, enabling the student’s aesthetic experience with the school space, bringing the art to daily life.